1997
DOI: 10.1111/1467-6486.00051
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Stakeholder Orientation in UK Companies and the Implications for Company Performance

Abstract: Orientation to the diverse interests of stakeholder groups is central to strategic planning, and failure to address the interests of multiple stakeholder groups may be detrimental to company performance. However, some companies may be unable to address all these interests, owing to a scarcity of resources, and the impact of multiple stakeholder orientation may be influenced by the environment. Despite calls by leading writers in the literature, there is no empirical evidence about the potential association of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
191
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(206 citation statements)
references
References 69 publications
4
191
0
Order By: Relevance
“…Indeed he is adamant that there is too much focus on cash flows and too little on the identification of the source of the brand's value. This is akin to other calls for more holistic approaches to the measurement of brand valuation 30,31 and also in line with current stakeholder thinking 32,33 where company performance is linked directly to a multiple stakeholder approach. The difficulty of this approach is that it makes the measurement of brand equity uncertain and takes us away from a clearly defined success criterion: the bottom line.…”
Section: Brand Value and Brand Equitysupporting
confidence: 62%
“…Indeed he is adamant that there is too much focus on cash flows and too little on the identification of the source of the brand's value. This is akin to other calls for more holistic approaches to the measurement of brand valuation 30,31 and also in line with current stakeholder thinking 32,33 where company performance is linked directly to a multiple stakeholder approach. The difficulty of this approach is that it makes the measurement of brand equity uncertain and takes us away from a clearly defined success criterion: the bottom line.…”
Section: Brand Value and Brand Equitysupporting
confidence: 62%
“…We have verified and found that all assumptions for regression are satisfied. There was no evidence of multicollinearity with all variable-inflation factors below the threshold of 5 (Hair et al, 2006).…”
Section: Analysis and Resultsmentioning
confidence: 78%
“…Several empirical works show a clear relationship between working with different special interest groups and efficient management of finances (Greenley et al 1997;(Freeman et al 2004).…”
Section: Stakeholders Consideredmentioning
confidence: 99%